Avaliação dos métodos diagnósticos e dos parâmetros hematológicos nas hemoparasitoses caninas no estado de Minas Gerais - Pâmela Cristina Lopes Gurgel Valente (2014)
Canine hemoparasitoses are diseases transmitted by vectors and commonly found in small animal veterinary routine. These diseases represent a historic and emerging problem in many countries of the world because of its high prevalence, relevance and public health risks, as some are considered zoonoses. The main hemoparasites found in Brazil are the following: Ehrlichia sp., Anaplasma sp., Babesia sp and Leishmania sp. The diagnosis of these pathogens is a major challenge in veterinary medicine which makes the subject of several studies. The aim of this study, was to investigate the hematological changes found in positive animals for them and compare methods for definitive diagnosis, defining sensitivity, specificity, positive and negative predictive value. In total, 93 dogs, coming from three different locations in the State of Minas Gerais, had samples of blood, bone marrow and lymph nodes collected, and then, was performed hematological, parasitological, serological and molecular examinations. Of all animals, 38.7% were positive for Ehrlichia canis, 23.6% for Anaplasma platys, 11.8% for Leishmania infantum/chagasi and 5.4% for Babesia sp. Considering the polymerase chain reaction (PCR) as gold standard, serological tests showed variation in sensitivity, ranging from 60.0% to 81.8%, with negative predictive values ranging from 80.9% to 95.8 %, and the direct parasitological methods obtained specificity ranging from 94.3% to 100 % with a positive predictive value of 33.3% to 100%. Evaluating the 54 animals with clinical symptoms 27 (50%) were positive for one or more agents in the PCR and of these, 18 (64.3%) were anemic, 17 (60.7%) thrombocytopenic and 10 (35,7 %) had abnormal global leukocyte. Relating the hematological changes with positive PCR for each hemoparasite studied, was observed statistically significant correlation (P < 0.05), only between animals positive for Ehrlichia canis witch presented anemia and thrombocytopenia. It was concluded in this study that in the absence of PCR for the diagnosis of canine hemoparasitoses, direct parasitological and serological methods should be involved and the hematological changes found in animals with clinical suspicion may direct the veterinarian, especially in diagóstico E. canis anemic and thrombocytopenic animals.